PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN LKPD PADA MATA PELAJARAN PKN DI UPT SPF SD INPRES BALANG BODDONG - Mirnawati Bakki; Mutmainnah Mutia Kahar; Nur Widiyana Anwar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve student learning outcomes in Civic Education through the use of Student Worksheets (LKPD) at UPT SPF SD Inpres Balang Boddong. Using Classroom Action Research method with two cycles, this study involved 17 fifth-grade students. The results showed a significant improvement in learning outcomes, with classical completeness increasing from 41.18% in cycle I to 100% in cycle II. The class average also increased from 73.17 to 86.35. The implementation of structured student worksheets not only improved cognitive aspects but also developed students' social skills and civic values. Positive transformation was observed in learning interaction patterns, with an increase in active student engagement from 65% to over 90%. This research proves that the use of well-designed student worksheets can be an effective solution in improving the quality of Civic Education learning at the elementary school level.